Review of Vasia Lekka’s, The Neurological Emergence of Epilepsy: The National Hospital for the Paralysed and Epileptic (1870–1895) - Ioannidis, Stavros (Historein, 2017)
Vasia Lekka. The Neurological Emergence of Epilepsy: The National Hospital for the Paralysed and Epileptic (1870-1895). New York: Springer, 2015. xiii + 209 pp.